Structural development and functional reconstitution in the olfactory system of the clawed frog Xenopus laevis - Kahl, Melina; Justus Liebig University Giessen (My University, 2025)
The transition of tetrapods to terrestrial habitats is concomitant with the adaptation of the olfactory system (OS) to the environment. This is reflected at the anatomical and functional levels with the formation of different subsystems, including cell subpopulations that exhibit distinct protein expression at the molecular level. The expression patterns of specific proteins vary between different species, although the olfactory systems show general anatomical similarities. For instance, in fish the calcium-binding protein S100Z is expressed in different cell types in their olfactory epithelium, while in mammals it is associated with cells within the vomeronasal organ (VNO). In the course of my thesis, I analyzed the expression pattern of S100Z in the OS of the anuran Xenopus laevis. Using immunohistochemistry in whole mount and slice preparations I identified a subgroup of S100Z expressing olfactory receptor neurons (ORNs) in the larval main OS and in the middle cavity of adult Xenopus laevis. In larval animals, these ORNs showed a lateral distribution bias in the olfactory epithelium and exclusively projected into the intermediate and lateral glomerular cluster. In conclusion, S100Z expression in the OS of Xenopus laevis is exclusively associated with the main OS and not with the VNO. Maintaining regenerative capacity is essential for the OS because of its exposed position to toxic substances or physical trauma. This capacity is attributed to the presence of two main cell types. Firstly, the basal cells of the olfactory epithelium, which are neuronal stem cells and support constant renewal by developing new supporting cells and ORNs. Secondly, the olfactory ensheathing cells (OECs), which enwrap the axons of ORNs until they project into the olfactory bulb (OB) in the forebrain. To date, the existence and role of OECs in the OS of Xenopus laevis have not been investigated in detail. I found vimentin expressing OECs enwrapping ORN axon bundles from the epithelium until the OB in larval Xenopus using immunohistochemistry. The presence of fibroblasts and macrophages in the olfactory nerve (ON) was determined through the utilization of immunohistochemistry and transgenic Xenopus lines. Unilateral ON transection induced a temporary transient and dynamic phosphorylation of the ribosomal protein S6 in these non-neuronal cells. In summary, I identified various cell types within the ON which protein expression is influenced by ON injury. The exact function of phosphorylated ribosomal protein S6 in the OS of Xenopus is still unknown.
Keywords: ddc:570